Adaptor protein APPL1 links neuronal activity to chromatin remodeling in cultured hippocampal neurons. (26th October 2020) - Wu, Yu; Lv, Xinyou; Wang, Haiting; Qian, Kai; Ding, Jinjun; Wang, Jiejie; Hua, Shushan; Sun, Tiancheng; Zhou, Yiting; Yu, Lina; Qiu, Shuang
Abstract: Local signaling events at synapses or axon terminals are communicated to the nucleus to elicit transcriptional responses, and thereby translate information about the external environment into internal neuronal representations. This retrograde signaling is critical to dendritic growth, synapse development, and neuronal plasticity. Here, we demonstrate that neuronal activity induces retrograde translocation and nuclear accumulation of endosomal adaptor APPL1. Disrupting the interaction of APPL1 with Importin α1 abolishes nuclear accumulation of APPL1, which in turn decreases the levels of histone acetylation. We further demonstrate that retrograde translocation of APPL1 is required for the regulation of gene transcription and then maintenance of hippocampal late-phase long-term potentiation. Thus, these results illustrate an APPL1-mediated pathway that contributes to the modulation of synaptic plasticity via coupling neuronal activity with chromatin remodeling.